Perioperative pain and inflammation after TAP block and wound infiltration - Musba, Andi Muhammad Takdir; Samad, Raehana; Sari, Andi Suci Kumala; Prasetyadhi, Jokevin (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Effective pain management after cesarean section is essential for promoting a smooth recovery. This study compares the efficacy of the transversus abdominis plane (TAP) block with local anesthetic infiltration as multimodal analgesia techniques in reducing pain intensity, time until first opioid requirement, and neutrophil-to-lymphocyte ratio (NLR) in post-cesarean patients under spinal anesthesia. Methods: This single-blind randomized clinical trial included 46 patients undergoing elective cesarean sections under spinal anesthesia. Patients were randomly assigned to receive either a TAP block or local anesthetic infiltration. Pain intensity, time until first opioid requirement, and NLR values were measured at various intervals post-surgery. Results: There were no significant differences in pain scores during movement between the two groups. However, the TAP block group showed significantly lower pain scores at rest 24 hours post-surgery, indicating a longer-lasting analgesic effect. The NLR values were significantly higher in the local anesthetic infiltration group at 24 hours. No postoperative opioid rescue was required in either group. Conclusions: Both TAP block and local anesthetic infiltration effectively manage post-cesarean pain. However, the TAP block may offer a more prolonged analgesic effect. Additionally, NLR may serve as a valuable predictor for postoperative pain. Further research is warranted to investigate the potential of NLR as a biomarker for postoperative pain management.